2017
DOI: 10.1371/journal.pone.0177443
|View full text |Cite
|
Sign up to set email alerts
|

Causal interactions in resting-state networks predict perceived loneliness

Abstract: Loneliness is broadly described as a negative emotional response resulting from the differences between the actual and desired social relations of an individual, which is related to the neural responses in connection with social and emotional stimuli. Prior research has discovered that some neural regions play a role in loneliness. However, little is known about the differences among individuals in loneliness and the relationship of those differences to differences in neural networks. The current study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 58 publications
(89 reference statements)
0
35
0
Order By: Relevance
“…The causal connection such as Granger causality analysis (GCA) reflected the directional flow of information between brain regions [15]. The causal relationship and adjustment patterns between different activation regions could be observed using GCA, which provided new insights for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…The causal connection such as Granger causality analysis (GCA) reflected the directional flow of information between brain regions [15]. The causal relationship and adjustment patterns between different activation regions could be observed using GCA, which provided new insights for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers revealed that the parahippocampal cortex and hippocampus were involved in memory [10][11][12][13]. The parahippocampal cortex played a role for spatial configuration of object in memory [14].…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that loneliness affects regions involved in social cognitions and empathy as well as emotional regulation. Perceived loneliness was predicted by effective connectivity of affective network to visual network and dorsal attentional network to ventral attentional network (Tian et al, ).…”
Section: Neuroimaging Of Social Exclusion and Lonelinessmentioning
confidence: 99%